Immunophenotypic Pattern and Treatment Outcome after Completion of Induction Remission in Children with Acute Lymphoblastic Leukemia (Journal of Current and Advance Medical Research, 2021)
Background: Acute lymphoblastic leukemia (ALL) is presented with different immunophenotypic pattern.Objective: The purpose of the study was to evaluate the immunophenotypic pattern of ALL and also, to recognize the frequency of different ALL subtypes and treatment outcome after induction remission therapy.Methodology: This prospective study was conducted in the Department of Paediatric Hematology and Oncology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from June 2017 to July 2018 for a period of one year. Newly diagnosed admitted cases of ALL aged 1 to 17.9 years were included. Immunophenotyping from aspirate marrow samples were done in a special hematology laboratory. Patients were monitored during induction remission period with physical examination and required investigations.Result: Among 87 analyzed patients, 81 patients (93.1%) were B-cell ALL and 6 patients (6.9%) were T-cell ALL. After completion of induction remission therapy 61 patients had undergone complete remission and among them B cell ALL were 56(69.1%) and T cell were 5(83.3%) (P=0.464). None of the patient had partial response or induction failure. Complication were developed in 53(60.91%) patients during induction therapy. Most common cause of death was septicemia (22/26). Death was more in patients who had total WBC count >50X109/L (p=0.017) and received regimen B (p=0.031).Conclusion: B cell ALL was more common and most of the patients had undergone complete remission after induction remission therapy.Journal of Current and Advance Medical Research, January 2021;8(1):59-64